OPERATIONALIZATION OF MARKETING CAPABILITIES IN THE CONTEXT OF ANALYTICS TECHNOLOGY ADOPTION - Daniel Peterson Silaban; Stanss L. H. V. J. Lapian; Altje L. Tumbel; Frederik G. Worang; Imelda W. J. Ogi (Universitas Pelita Harapan, 2023)
The advent of analytics has been considered as a revolution in how firms treat data. However, the implementation of this technology is still an issue for researchers and practitioners. Many business leaders still reluctant to adopt this technology since it is still unclear how analytics adds value on firms. There are limited studies that incorporate analytics and capabilities, particularly in marketing. Moreover, there is also lack of empirical studies that cover the adaptive side of marketing capabilities. This study aims to close the gap by constructing a sound and holistic measurement of firms’ marketing capabilities (MCs) to measure the impact of analytics-related adoption. Integrative literature review was carried out to synthesize previous MCs constructs. Then, analysis was conducted to develop a new construct of MCs measurement. The result of this study proposes a more detailed and comprehensive framework in understanding the impact of marketing analytics (MA) adoption on all dimensions of MCs, including adaptive side of MCs.